2013
DOI: 10.1039/c3ta01665j
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of platinum clusters on titania nanoparticles at atmospheric pressure

Abstract: We report the fabrication of platinum nanoclusters with a narrow size distribution on TiO 2 nanoparticles using atomic layer deposition. With MeCpPtMe 3 and ozone as reactants, the deposition can be carried out at a relatively low temperature of 250 C. Our approach of working with suspended nanoparticles at atmospheric pressure gives precise control of the material properties, high efficiency of the use of the platinum precursor, and the possibility for large-scale production of the nanostructured particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 33 publications
2
79
0
Order By: Relevance
“…13 However, vacuum conveying would also be possible. 37 Operation under vacuum conditions is often preferred to facilitate a higher concentration of the precursors under the selected vaporization temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 However, vacuum conveying would also be possible. 37 Operation under vacuum conditions is often preferred to facilitate a higher concentration of the precursors under the selected vaporization temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that batch-wise ALD on nanoparticles works very well in a fluidized bed. 3,13 During fluidization, the nanoparticles form agglomerates with a very open, fractal nature enabling a good access of precursors to the surface. [34][35][36] In temporal ALD, this has led to a very good dispersion of deposited material over the particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition scheme involves the sequential exposure of the support material to MeCpPtMe 3 and ozone (Goulas and van Ommen, 2013) at 250°C. The ALD reaction proceeds via a mechanism proposed by Kessels et al (2009) adapted to the following generic scheme:…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the atmospheric pressure operation of a fluidized bed ALD reactor was demonstrated for the growth of thin films (Beetstra et al, 2009) and the deposition of highly-dispersed nanoparticles (Goulas and van Ommen, 2013). Although the pulsing times required are longer than the equivalent in low-pressure operation, the process was proven to be efficient in terms of precursor utilization while excluding the need for expensive vacuum equipment.…”
Section: Reactor Technologymentioning
confidence: 99%